Repurposing Ziyuglycoside II Against Colorectal Cancer via Orchestrating Apoptosis and Autophagy - Bai, Can; Zhang, Zhe; Zhou, Li; Zhang, Huan-Yu; Chen, Yan; Tang, Yong (Frontiers in Pharmacology, 2020)
Effective chemotherapy drugs for colorectal cancer remain a challenge. In this research, Ziyuglycoside II (Ziyu II), exhibits considerable antitumor activity against CRC cells both in vitro and in vivo. The results showed that Ziyu II induced apoptosis through the accumulation of reactive oxygen species (ROS), which was necessary for Ziyu II to inhibit colorectal cancer cells. Intriguingly, The treatment of Ziyu II triggered complete autophagic flux in CRC cells. Inhibition of autophagy partially reversed Ziyu II-induced growth inhibition, demonstrating a cytotoxic role of autophagy in response to Ziyu II-treated. Mechanism indicated that Ziyu II-induced autophagy by inhibiting Akt/mTOR pathway. Akt reactivation partially reduced Ziyu II-induced LC3-II turnover and LC3 puncta accumulation. Especially, Ziyu II improves the sensitivity of 5-fluorouracil which is the first-line chemotherapy drug in colorectal cancer cells. This research provides novel insight into the molecular mechanism of Ziyu II’s anti-proliferation, including apoptosis and autophagy, and lays a foundation for the potential application of Ziyu II in clinical CRC treatment.